A Yiddish World Remembered - Goldberg, Andrew; Gould, Elliott (Shanachie Entertainment, 2010)
In "A Yiddish World Remembered", the story of Jewish life in Eastern Europe is brought to life again by some of the remaining eyewitnesses. Narrated by Academy Award nominated actor Elliott Gould and accompanied by never-before-seen archival films, vintage photographs, and, of course, traditional Klezmer and cantorial music, the documentary takes a realistic and enlightening look at this unique and all-but-vanished way of life. For those in rural communities, there was often no running water or electricity. For many, anti-Semitism was a part of daily life. But for everyone, crowded conditions and poverty seemed to prevail. Despite these trials, through the eyes of the individuals interviewed, we learn that Jewish communities were close-knit and often even joyous places to live. This television special explores everything from the fascinating language of Yiddish to the Rabbis and Rebbes that often ran the communities to the powerful Jewish movements of Khasidism, Bundism and Zionism. [www.amazon.com]